What Can a Stylometric Analysis Contribute to the Diary of Saint Faustina Kowalska? - Isea, Raúl (Journal of Current Scientific Research, 2024)
Saint Maria Faustina Kowalska's Diary records the words of Christ revealed to her between 1934 and 1938. The frequency of the words used by God and Sor Faustina could be statistically determined by stylometric analysis since each has its own linguistic footprint. To do this, we analyze various parts of the Diary in three different editions (Polish, Spanish, and English). The results show a linguistic style characteristic of Sister Faustina and another to God. So this paper confirms that there was a conversation between the two.
Keywords: Stylometric Analysis; Linguistic Footprint; Linguistic Style; Diary; Conversation